Implementation of Culinary Business Management in Student Careers with Entrepreneurship Education in The Creative Industries - Gusnita, Wiwik; Giatman, M; Syah, Nurhasan (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
Graduates of the D3 Culinary Study Program are expected to create their own fields through entrepreneurship. Through entrepreneurship, students are able to develop their mindset to have the courage to open their own job opportunities. This article aims to determine the role of entrepreneurship education in business management in the culinary sector during culinary business management learning. This research method uses quantitative descriptive techniques with Product Moment correlation. The population of this study was 28 IKK D3 Culinary students who were randomly selected who had taken the practical course in Catering Business Management. The results of the research show that there is an influence of entrepreneurship education on the management of catering businesses with rhit results greater than the rtable value with a significance level of 5% and df 26, namely the rhit value of 0.375 and the rtable value of 0.086. It was concluded that the role of entrepreneurship education on food business management has a high level of influence, if students cannot implement management knowledge to start an entrepreneur, then students will not be able to run a food business